The Extension of Collective Agreements Within Collective Bargaining at Company Level - Monteblanco Vinces, Alejandro (2016)
In this article, a review is conducted to the implementation of Peruvian law of collective agreements and their impact at company level. To achieve this purpose, in principle we mentioned what the Peruvian labor laws and their current application, and then compared with other Latin American visions, and finally outline a more peaceful solution considering the guidelines of the International Labour Organization labor standards and our constitutional current.